The Effectiveness of using simulation in laboratory class in improving clinical skills of midwifery students in the prevention of postpartum hemorrhage in Kampong Cham Regional Training Center - Duch Sophath
This study tested the effectiveness of simulation in teaching clinical skills of prevention of postpartum hemorrhage (PPPH). This skill is a basic competency expected of midwives in Cambodia with a high maternal mortality rate of 472 per 100,000 live births. The study was conducted at Kampong Cham Regional Training Center, Kingdom of Cambodia. The study determined the difference in knowledge of third year midwifery students before and after training using simulation. Also assessed were the clinical skills of the student midwives following simulation for prevention of postpartum hemorrhage (PPPH). The study used an experimental design, using a modified World Health Organization (WHO) training package as the research instrument for the experimental group and compared with the usual classroom lecture and laboratory sessions composing the control group. All third year students (N=80) students were given a questionnaire, composed of 20 items dealing with basic knowledge of PPH and 15 items on clinical skills in managing PPH. Respondents accomplished the questionnaire twice: before and after the intervention. There was a total response rate of 100%. Results showed that the pre-test scores of the control group had an overall mean of 35% and the post-test mean was 40%. There was a statistically significant difference of the pre-test and post-test means of the control group (p = 0.017). The overall mean rating of the pre-test of the experimental group was 36% and post-test mean of 66%. The difference in the pre-test and post-test means was statistically significant (p =0.000). Both groups in the pretest had similar results. After intervention, the third year midwifery students who received modified WHO Training Package had higher knowledge and skills scores than the group who used Traditional Teaching Method in terms of knowledge. The difference between the control and experimental group posttest means was statistically significant (p = 0.000). The results indicate that using simulation in clinical teaching improves the knowledge and skills of midwifery students in the prevention and management of postpartum hemorrhage better than the traditional lecture method.